Challenges and Opportunities for Developing Intercultural Competences in Language Teaching in Grammar Schools - Pulko, Simona (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
Intercultural and multilingual competence is an individual’s ability to participate effectively in a multilingual and multicultural society. In education, such competence is developed through language learning, awareness of one’s own identity, and at the same time through understanding, experiencing, and putting into practice multilingual, plurilingual, and intercultural realities. A student can communicate in several languages and express positive attitudes and values toward his own culture as well as other cultures. The paper presents an analysis of the representation of such content (and goals) in curricula for grammar schools (2011 and 2025) as well as in the textbooks Slovenščina 1–4: moč jezika, focusing on the challenges and opportunities these materials offer.